2021
DOI: 10.1021/acs.analchem.0c05027
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Vacancy Engineering in Graphitic Carbon Nitride for Strong, Stable, and Wavelength Tunable Electrochemiluminescence Emissions

Abstract: As an attractive electrochemiluminescence (ECL) emitter, graphitic carbon nitride (CN) still suffers from weak and unstable ECL signals for its poor conductivity and the occurrence of electrode passivation. In this study, a simple nitrogen vacancy (NV) engineering strategy has been developed for the improvement of ECL performances (intensity and stability) for the first time. In comparison to pristine CN (RSD = 51.98% for 10 continuous scan), ca. 60 times amplification in ECL intensity and 70 times enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 44 publications
2
75
0
Order By: Relevance
“…Electrochemiluminescence (ECL) is the phenomenon of electrochemically controlled chemiluminescence in which the ECL luminophores generate excited states through electron transfer reactions at the surface of electrode and then emit light. Because of its multiple merits such as high sensitivity, wide dynamic response range, fast response speed, and low background signal, ECL is becoming a typical analysis method for many application fields, e.g., clinical diagnosis, bioanalysis, food analysis, environmental monitoring, and so on. In order to realize these applications, ongoing interest is focusing on the development of qualified ECL luminophores with high ECL efficiency and stability. , Among them, graphite-like carbon nitride (g-C 3 N 4 ) is a promising candidate, , since it is unique in nontoxic, facile synthesis, low cost, and excellent biocompatibility. , In 2012, Xiao and Choi et al reported the first g-C 3 N 4 ECL, in which the g-C 3 N 4 /K 2 S 2 O 8 ECL couple was used to trace detection on Cu 2+ with a detection limit of 0.9 nM . After that, g-C 3 N 4 nanosheets were dominantly applied in the topic of g-C 3 N 4 ECL. However, restricted by poor conductivity, charge accumulation and the electrode passivation effect, those g-C 3 N 4 ECL frequently suffered from low stability and/or low ECL efficiency, which greatly limits its applications. , To overcome these issues, many researchers focus on modifying the chemical structure of g-C 3 N 4 nanosheets in different methods, such as noble metal load (Au-g-C 3 N 4 ), heteroatom doping (P-g-C 3 N 4 ), , nitrogen vacancy engineering (NV-g-C 3 N 4 ) . Despite this progress, g-C 3 N 4 nanomaterials suitable for ECL are still scarce.…”
mentioning
confidence: 99%
“…Electrochemiluminescence (ECL) is the phenomenon of electrochemically controlled chemiluminescence in which the ECL luminophores generate excited states through electron transfer reactions at the surface of electrode and then emit light. Because of its multiple merits such as high sensitivity, wide dynamic response range, fast response speed, and low background signal, ECL is becoming a typical analysis method for many application fields, e.g., clinical diagnosis, bioanalysis, food analysis, environmental monitoring, and so on. In order to realize these applications, ongoing interest is focusing on the development of qualified ECL luminophores with high ECL efficiency and stability. , Among them, graphite-like carbon nitride (g-C 3 N 4 ) is a promising candidate, , since it is unique in nontoxic, facile synthesis, low cost, and excellent biocompatibility. , In 2012, Xiao and Choi et al reported the first g-C 3 N 4 ECL, in which the g-C 3 N 4 /K 2 S 2 O 8 ECL couple was used to trace detection on Cu 2+ with a detection limit of 0.9 nM . After that, g-C 3 N 4 nanosheets were dominantly applied in the topic of g-C 3 N 4 ECL. However, restricted by poor conductivity, charge accumulation and the electrode passivation effect, those g-C 3 N 4 ECL frequently suffered from low stability and/or low ECL efficiency, which greatly limits its applications. , To overcome these issues, many researchers focus on modifying the chemical structure of g-C 3 N 4 nanosheets in different methods, such as noble metal load (Au-g-C 3 N 4 ), heteroatom doping (P-g-C 3 N 4 ), , nitrogen vacancy engineering (NV-g-C 3 N 4 ) . Despite this progress, g-C 3 N 4 nanomaterials suitable for ECL are still scarce.…”
mentioning
confidence: 99%
“…Figure 4F displays that the ECL intensity of the GDY under consecutive potential scans remained constant with a relative standard deviation (RSD) of 2.5 %, revealing that the ECL signals of GDY were highly repeatable. ECL efficiency (Φ ECL , %) was determined in reference to that of Ru(bpy) 3 Cl 2 /K 2 S 2 O 8 using the reported equation: [13f, 17a, 29] …”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6] Recently, multicolor ECL has attracted considerable attention for ECL-based biomedical applications ranging from multiplex bioassay to bioimaging, raising an increasing demand for exploiting luminophores with tunable emission wavelength. [7][8][9][10][11] However, the development of multicolor ECL-based biomedical applications was somewhat restricted. In this context, it has been reported that multicolor ECL could be realized by combining or modifying ruthenium (II) and iridium (III) complexes.…”
Section: Introductionmentioning
confidence: 99%